This littler light : some thoughts on not changing the world : a memoir - DeConto, Jesse James (Eugene, Oregon : Cascade Books, 2013)
Like other evangelical kids, Jesse James DeConto felt called to shine the light of truth into the world. His job as a journalist and his young marriage, though, would radically change him. First, he learned that Christians have no corner on truth: Working out in the world, trying to be the "Roaring Lamb" he'd been trained to be, he met atheists and agnostics who seemed to do better at embodying Christian love than many Christians did. Confessing the church's failures was one thing, but the author had to face his own weakness the hard way, when the cheap threads that held his marriage intact finally snapped. Jesse found himself at the end of his twenties with a broken bank account, a broken body, and a broken family. In the midst of that pain, he discovered his brokenness better equipped him to share God's grace than his striving ever had. He learned to say with theologian Karl Barth that "his importance may consist in his poverty, in his hopes and fears, in his waiting and hurrying, in the direction of his whole being toward what lies beyond his horizon and beyond his power"
Keywords: DeConto, Jesse James; Evangelists -- United States -- Biography